2012
DOI: 10.1161/strokeaha.111.629246
|View full text |Cite
|
Sign up to set email alerts
|

Stroke and Long-Term Exposure to Outdoor Air Pollution From Nitrogen Dioxide

Abstract: Background and Purpose-Years of exposure to tobacco smoke substantially increase the risk for stroke. Whether long-term exposure to outdoor air pollution can lead to stroke is not yet established. We examined the association between long-term exposure to traffic-related air pollution and incident and fatal stroke in a prospective cohort study. Methods-We followed 57 053 participants of the Danish Diet, Cancer and Health cohort in the Hospital DischargeRegister for the first-ever hospital admission for stroke (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 36 publications
(67 reference statements)
3
91
1
Order By: Relevance
“…Current scientific evidence links short-term NO 2 exposures, ranging from 30 min to 24 h with adverse respiratory effects including airway inflammation in healthy people and increased respiratory symptoms in people with asthma. It also contributes to cardiovascular diseases, adverse birth outcomes, premature death and cancer (Andersen et al, 2012;Beelen et al, 2008;Kan and Jia, 2003;Kan et al, 2009;Michiels et al, 2012;Qian et al, 2007;Villeneuve et al, 2012;Yorifuji et al, 2013;Yu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Current scientific evidence links short-term NO 2 exposures, ranging from 30 min to 24 h with adverse respiratory effects including airway inflammation in healthy people and increased respiratory symptoms in people with asthma. It also contributes to cardiovascular diseases, adverse birth outcomes, premature death and cancer (Andersen et al, 2012;Beelen et al, 2008;Kan and Jia, 2003;Kan et al, 2009;Michiels et al, 2012;Qian et al, 2007;Villeneuve et al, 2012;Yorifuji et al, 2013;Yu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, exposure to nitrogen dioxide was associated with admissions, denoting a more severe picture in a prospective cohort study (Andersen et al, 2012). The study identified significant associations between NO 2 exposure and stroke incidence and also fatal stroke during a follow-up of about 10 years.…”
Section: Resultsmentioning
confidence: 74%
“…None of the studies [53,[55][56][57][58] distinguished between ischemic and hemorrhagic stroke. A case-control study of ischemic stroke hospitalizations in Sweden failed to detect associations with air pollution [59], whereas a recent cohort study, the first with data on both stroke types, reported significant associations with the ischemic but none with hemorrhagic stroke [60].…”
Section: Strokementioning
confidence: 93%
“…The current evidence is conflicting [53][54][55][56][57][58][59][60]. A cohort of American women showed an association between air pollution and stroke incidence [53], whereas an American [55] and Norwegian [56] cohorts failed to detect association with stroke mortality.…”
Section: Strokementioning
confidence: 99%